2007
DOI: 10.1016/j.brainres.2007.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Here I am: The cortical correlates of visual self-recognition

Abstract: Recently, interest in the neural correlates of self-recognition has grown. Most studies concentrate on self-face recognition. However, there is a lack of convergence as to precise neuroanatomical locations underlying self-face recognition. In addition, recognition of familiar persons from bodies has been relatively neglected. In the present study, cerebral activity while participants performed a task in which they had to indicate the real appearance of themselves and of a gender-matched close colleague among i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
180
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(194 citation statements)
references
References 58 publications
10
180
2
2
Order By: Relevance
“…This finding is in accord with previous studies showing a preferential processing of self-images compared to other images (Devue et al, 2007;Frassinetti et al, 2009Frassinetti et al, , 2011Knoblich & Prinz, 2001;Serino et al, 2008;Sugiura et al, 2006;Uddin et al, 2005). Note that whereas most studies -in which the picture was relevant to the subject's task -have found a decrease in RT to self-images compared to images of others, the slower responses to self-images found in the present study were obtained in response to task-irrelevant stimuli.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in accord with previous studies showing a preferential processing of self-images compared to other images (Devue et al, 2007;Frassinetti et al, 2009Frassinetti et al, , 2011Knoblich & Prinz, 2001;Serino et al, 2008;Sugiura et al, 2006;Uddin et al, 2005). Note that whereas most studies -in which the picture was relevant to the subject's task -have found a decrease in RT to self-images compared to images of others, the slower responses to self-images found in the present study were obtained in response to task-irrelevant stimuli.…”
Section: Discussionsupporting
confidence: 93%
“…The results indicated that self-recognition was faster than recognition of a stranger, for both faces and bodies, regardless of stimulus type (Sugiura et al, 2006). Several other studies have shown an advantage for processing and recognition of the own body (Devue et al, 2007) and body parts (Frassinetti et al, 2009;Salomon, Malach, & Lamy, 2009). Taken together these findings show that our own visual body image (face, body or body parts) enjoys privileged processing which is governed by specific brain mechanisms.…”
Section: Introductionmentioning
confidence: 70%
“…In spite of this, very few children (16%) failed the picture task, even under the relatively difficulty conditions through which the distractor faces had been selected to be as similar as possible to the subject. This result is in line with other studies showing that our own representation in processed in a specific way (Devue & Brédart 2008;Devue, Collette, Balteau, Degueldre, Luxen, Maquet & Brédart, 2007). It clearly follows from this argument that picture self-recognition task does not only assesses familiarity with certain facial features, but effectively constitutes one component of self-awareness.…”
Section: Three Levels Of Explicit Self-awareness 19supporting
confidence: 91%
“…Because faces capture attention, one has to assume that faces are discriminated by some`pre-attentive' or unconscious processing (Theeuwes and Van der Stigchel 2006). Current findings suggest that the discrimination between a face and a non-face configuration could be based on this early pre-attentive processing (that could take place in the occipito-temporal cortexösee Devue et al 2007). However, in order to discern the identity of the face, a second`attentive' processing stage (possibly originating in the fusiform gyrus ösee Devue et al 2007) may be necessary.…”
Section: Discussionmentioning
confidence: 81%